2011
DOI: 10.1590/s0100-879x2010007500149
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of bidirectional gene pairs by 17-β-estradiol in MCF-7 breast cancer cells

Abstract: Using cDNA microarray analysis, we previously identified a set of differentially expressed genes in primary breast tumors based on the status of estrogen and progesterone receptors. In the present study, we performed an integrated computer-assisted and manual search of potential estrogen response element (ERE) binding sites in the promoter region of these genes to characterize their potential to be regulated by estrogen receptors (ER). Publicly available databases were used to annotate the position of these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Many members of the Thioredoxin family are mainly involved in the redox reaction of the body. It is highly expressed in many solid tumors such as liver cancer [ 14 ], colon cancer [ 31 ], breast cancer [ 32 ] and so on. Other experiments showed that TXNDC9 was up-regulated in some oxaliplatin-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Many members of the Thioredoxin family are mainly involved in the redox reaction of the body. It is highly expressed in many solid tumors such as liver cancer [ 14 ], colon cancer [ 31 ], breast cancer [ 32 ] and so on. Other experiments showed that TXNDC9 was up-regulated in some oxaliplatin-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well known that methylation of the binding sites for GABPA (which is highly enriched at bidirectional promoters [11]) is inhibited by DNA methylation [34], particularly at the BRCA1 promoter [4,31]. Finally, a very recent report suggests that estrogen controlled genes with estrogen receptor binding sites close to the proximal promoter are over-represented by bidirectional promoters, an observation that merits future exploration [15]. …”
Section: Introductionmentioning
confidence: 99%
“…eIF5B, reported to be the most catalytically active of the translation initiation factors ( 49 ), was one of the top 25 proteins regulated. Interestingly, this protein was previously demonstrated to be increased by E2 in MCF-7 estrogen-responsive breast cancer cells via ER ( 50 ).…”
Section: Discussionmentioning
confidence: 98%